Cuttlefish (Sepia Spp) Identification and Biological Analysis of A Dominant Cuttlefish Species Landed in Muncar, Banyuwangi Regency, East Java. - Daduk Setyohadi; Sunardi Sunardi; Nurul Mukhlis; Citra Nilam Cahya (Research Journal of Life Science, 2016)
Identification and biological analysis of Cuttlefish (Sepia spp) this could be the basis of information for cuttlefish resource management for sustainability. The aims of this study were to determine the species composition of cuttlefish, determine similarity in morphology among cuttlefish species, and length-weight relationship of dominant species cuttlefish landed in Muncar, Banyuwangi, East Java. The analytical method used is species composition analyze, Hierarchical clustering analysis to determine similarity among cuttlefish species and length-weight relationship analysis of dominant cuttlefish species with the following equation W = aLb. There are three species of cuttlefish were landed in Muncar, Banyuwangi, Sepia pharaonis with 373 individuals (92.6%), Sepia latimanus 19 individuals (4.7%), and Sepia esculenta 11 individuals (2.7%). The results of length-weight relationship analysis cuttlefish dominant species, Sepia pharaonis, the b values obtained in the total sample, males and females respectively are 2.55, 2.56, and 2.57. It shows that the growth properties of S. pharaonis is negative allometric. It means the population has thin body shape where the increase in length faster than weight gain.